Arsitektur Rumah Tinggal Jepang untuk Masyarakat Umum - Nurdiani, Nina (Bina Nusantara University, 2014)
The form of Japanese residential architecture throughout its history shows its own uniqueness. The success of the Japanese government to provide housing for its citizens supports the study to know how Japanese residential architecture for the public society happened until today. The study of Japanese residential architecture for the public society was conducted by the descriptive approach. Data were collected through literature study from the history and development of Japanese residential architecture for public society and also done by field observations in Tokyo and surrounding cities. The study results the knowledge about many forms of residential architecture to public society since before the world war until now and provides knowledge relating to the successful provision of public housing so that it can be accepted by the occupants. The study is expected to provide inputs for the development of programs for public housing provision in urban areas in Indonesia.